THE POTENTIAL EFFECT OF AVOCADO SEED EXTRACT (PERSEA AMERICANA) AS A CORROSION INHIBITOR ON SURFACE CHARACTERISTIC OF ORTHODONTIC WIRES - Leliana Sandra Devi; Rina Sutjiati; Dwi Prijatmoko; Herniyati; Rudy Joelijanto; Vanda Ramadhani (Journal of Vocational Health Studies, 2025)
Background: The surface roughness of orthodontic arch wires is an essential factor that affects the effectiveness of arch-guided tooth movement. Metal wires exposed to the oral cavity environment are susceptible to corrosion. The corrosion process cannot be stopped but can be inhibited using natural inhibitors that contain antioxidant compounds, such as tannins found in avocado seeds. Tannins in avocado seed extract can act as a corrosion inhibitor through two working mechanisms, a passive layer and an adsorption process. Purpose: The aim of this study was to examine the viability of avocado seed extract as a corrosion inhibitor on the surface characteristic of orthodontic wires. Method: This research is an experimental laboratory research.  A total of 48 orthodontic wires (stainless steel, nickel titanium, and Titanium-Molybdenum Alloy (TMA)) were prepared and divided into control and treatment groups. The treatment groups were immersed in avocado seed extract at concentration of 1.5 g/L (T-1), 2 g//L (T-2) and 2.5 g/L (T-3) for 7 days with twice daily immersion of 1 minute each. A TR 220 surface roughness tester (ΔRa) was used to evaluate surface characteristic. The data was analyzed using the one-way ANOVA test followed by post hoc LSD test with a significance value of p-value < 0.05. Result: The average surface roughness increased in all control groups except for stainless steel wire which did not show a significant difference with p-value = 0.716. Furthermore, the difference test between groups on each wire showed different results. Conclusion: Avocado seed extract is effective as a corrosion inhibitor for orthodontic wires.